Persepsi Korupsi Pajak, Transparansi Pajak dan Norma Ekspektasi Terhadap Kepatuhan Wajib Pajak - Kairun Nisa, Mia; Syaf Putra, Rudi; Hetri Suriyanti, Linda (Politeknik Negeri Jakarta, 2025)
This study aims to determine the effect of tax corruption perception, tax transparency, and normative expectations on the compliance of individual taxpayers. The research was conducted on individual taxpayers registered at the KPP Pratama Pekanbaru Senapelan, with a total of 100 respondents. The method used is a quantitative approach with data collection carried out through the distribution of questionnaires. The collected data were analyzed using descriptive statistics, data quality tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing with the help of SPSS version 25 software. The results of the study indicate that tax corruption perception, tax transparency, and normative expectations have a significant influence on taxpayer compliance. Thus, it can be concluded that the higher the perception of tax corruption, the better the tax transparency, and the stronger the normative expectations perceived by individual taxpayers, the higher their level of tax compliance. Keywords: Taxpayer compliance; tax corruption perception; tax transparency; expectancy norms.